Do urban tourists prefer vegetarianism? An urban-rural comparison of vegetarian consumption in China - Chen, Guoyi; Tan, Wei; Ran, Ning; Zhang, Jiansheng; Yan, Bangquan (Frontiers in Nutrition, 2022)
The adoption of a vegetarian diet might have public health and environmental benefits. However, little is known about urban and rural Generation Z tourists' attitudes toward vegetarianism or vegetarian consumption within the Chinese urban and rural settings. Hence, to address this gap, the present study adopted a sequential and mixed research approach based on a survey (n = 212) and laddering interviews (n = 20) to validate post-millennial tourists' motives for adopting a vegetarian diet. The results identified the top four motives as environmental protection and resource conservation, ethical consideration, personal taste and choice, and personal healthcare issues. The top four barriers to vegetarianism were unavailability and limited choice, peer pressure, traditional prejudice/habit, and the inability to change. The results also demonstrated that both rural and urban tourists adopt vegetarianism mainly for environmental protection and ethical consideration, a subtle difference between them is that urban vegetarians emphasized ethical considerations more but rural ones emphasized food and variety. Urban consumers considered unavailability and limited choice as the topmost barriers to being vegetarian, while rural vegetarians found traditional prejudice to be restricting. Due to traditional dietary habits and peer influence, rural tourists face many more challenges when adopting a vegetarian diet. Understanding the perceived benefits and barriers to being vegetarian in different regions will not only enrich the theory of food nutrition but also expand Generation Z tourists' consumption behavior and practices.